(untitled) (Research, Society and Development, 2022)
Assisted reproduction techniques are therapeutic resources aimed at the possible pregnancy of couples with difficulties in the process of natural pregnancy, given that infertility is a public health problem. The unified health system, through laws and ordinances, provides for the realization of this therapy, making possible the realization of a dream of life of the couple through any economic acquisition. Therefore, this study aims to raise scientific knowledge about the achievements of assisted reproduction techniques by the unified health system. This is an Integrative Literature Review with information collected in the following databases: Latin American and Caribbean Health Sciences, Nursing Database and Scientific Electronic Library Online. A total of 178 scientific articles were found, and, after establishing the inclusion and exclusion criteria, the final sample consisted of 03 publications. The laws and ordinances that make the implementation possible have been in existence for more than a decade, and, even so, there are difficulties in the implementation in its entirety. Therefore, in view of the government’s legal responsibility to guarantee the integral practice of reproductive rights based on the Constitution, public policy interventions are necessary to identify and resolve flaws in the functioning of the system, in order to guarantee the assistance of couples. infertile.